Guidelines for Implementation of Social Credit Systems in Thailand: Mechanisms to Motivate and Control People's Behavior - Tarat, Saranya; Songmuang, Pokpong; Sindecharak, Teera (Journal of Multidisciplinary Academic Research and Development (JMARD), 2024)
Social control is one of the important mechanisms that lead to the creation of a systematic society, enabling citizens to coexist peacefully. The social credit system is one of the moral forms of social control that the state has established to control citizens' behavior. The operation of the social credit system is coupled with a process of reward and punishment to make members of society aware of the consequences of their actions and to discourage them from engaging in behavior that may have negative effects on themselves. The implementation of the social credit system in each country varies according to the political, governmental, and cultural context of that country. If Thailand adopts the concept of the social credit system, a suitable plan must be devised according to the social context. This research aims to study the implementation of the social credit system in Thailand by reviewing case studies from the United States of America and the People's Republic of China, along with interviews with organizations and individuals from the government sector, private sector, civil society, and the public. The results show that the implementation of the social credit system in Thailand should focus on stimulating negative behavior by transforming it into measurable scores. These scores can then be exchanged for rights and benefits, encouraging positive behavior.